DOES THE USE OF GUIDED QUESTIONS IN TUTORIAL SYSTEM IMPROVE STUDENTS’ SPEAKING ABILITY? - Sukmawati Yasim (LP2M IAIN Sultan Amai Gorontalo, 2019)
This research aimed to find out whether or not the use of guided questions in Tutorial System improved the students’ speaking ability of Easy Speak. Easy Speak was an English course situated in Makassar. The method of this research was pre-experimental. In collecting data, the researcher used speaking test in pre-test and post-test. The population of the research was 737 students. In this research, the researcher used purposive sampling technique which consisted of 25 students. The results of this research showed that the mean score of pre-test were 62,17 and 75,15 in post-test and the value of t-test was 7,23 which is greater than t-table 2.05 at the level of significance (α) = 0.05, so the null hypotheses was rejected, and alternative hypotheses (H1) was accepted. The researcher concluded that there was significant difference of the students’ speaking ability of Easy Speak after giving treatment using guided questions.